Pengaruh CaCO3 terhadap Kualitas Plastik Biodegradable Berbasis Selulosa Bakteri Sorbitol dari Air Kelapa - Safhira, Elsa; Putra, Ananda (Journal of Natural Sciences, 2024)
Plastic is one of the most commonly used materials in society. The accumulation of plastic waste has a negative impact on the environment and human health. To mitigate these effects, there has been a shift toward environmentally friendly packaging. Biodegradable plastic is an eco-friendly material because it can be easily degraded by microorganisms. This study aims to investigate the effect of varying CaCO3 additive concentrations on the quality of biodegradable plastic based on bacterial cellulose-sorbitol from coconut water. The study includes testing mechanical properties, biodegradability, and analysis using FTIR and XRD instruments. In this research, 30% sorbitol was used as a plasticizer, and CaCO3 was added in varying amounts: 2 g, 4 g, 6 g, and 8 g. The results of the mechanical property tests showed a tensile strength of 179.85 MPa at 8 g of CaCO3 addition, which meets the SNI (Indonesian National Standard) range for conventional plastic (24.7–302 MPa). The elasticity was 906.21 MPa, and the elongation value was 31.50%. Biodegradability tests revealed that plastic with CaCO3 showed increased degradation, with 90% degradation observed by day 15. FTIR functional group analysis showed no new functional groups, while XRD analysis indicated that the addition of CaCO3 increased the crystallinity of the plastic to 96.92%, compared to 95.79% for bacterial cellulose-sorbitol without CaCO3.